Extended kinetic method and RRKM modeling to reinvestigate proline's proton affinity and approach the meaning of effective temperature. Issue 2 (April 2019) - Lesage, Denis; Mezzache, Sakina; Gimbert, Yves; Dossmann, Héloïse; Tabet, Jean-Claude
Proline proton affinity PA(Pro) was previously measured by extended kinetic methods with several amines as reference bases using a triple quadrupole mass spectrometer ( J Mass Spectrom 2005; 40: 1300). The measured value of 947.5 ± 5 kJ.mol −1 differs by more than 10 kJ.mol −1 from previous reported experimental or calculated values. This difference may be explained in part by the existence of relatively large entropy difference between the two dissociation channels (ΔΔS ‡ avg  = 31 ± 10 J.mol −1 .K −1 ) and by the inaccuracy of the amines proton affinity used as reference bases. In the present work, these experimental measurements were reinvestigated by RRKM modeling using MassKinetics software. From this modeling, a new PA value of 944.5 ± 5 kJ.mol −1 and a ΔΔS ‡ avg(600K) value of 33 ± 10 J.mol −1 .K −1 are determined. However, the difference between experiment and recent theoretical calculations remains large (10 kJ.mol −1 ). These RRKM simulations allow also accessing to the effective temperature parameter (T eff ) and to discuss the meaning of this term. As previously reported, T eff mainly depends on the internal energy and on the decomposition time as well. It also depends on the critical energies and on the transition state. Considering the entrance of the collision cell as a new ion source, T eff is finally shown to be close to a characteristic temperature (T char ).